β-heavy-spectrin stabilizes the constricting contractile ring during cytokinesis - Silva, AM (2022)
Cytokinesis requires the constriction of an actomyosin-based contractile ring and involves multiple F-actin crosslinkers. We show that partial depletion of the C. elegans cytokinetic formin generates contractile rings with low F-actin levels that constrict but are structurally fragile, and we use this background to investigate the roles of the crosslinkers plastin/PLST-1 and β-heavy-spectrin/SMA-1 during ring constriction. We show that the removal of PLST-1 or SMA-1 has opposite effects on the structural integrity of fragile rings. PLST-1 loss reduces cortical tension that resists ring constriction and makes fragile rings less prone to ruptures and regressions, whereas SMA-1 loss exacerbates structural defects, leading to frequent ruptures and cytokinesis failure. Fragile rings without SMA-1 or containing a shorter SMA-1, repeatedly rupture at the same site, and SMA-1::GFP accumulates at repair sites in fragile rings and in rings cut by laser microsurgery. These results establish that β-heavyspectrin stabilizes the constricting ring and reveals the importance of β-heavy-spectrin size for network connectivity at low F-actin density.